Analysis of Credit Restructuring Implementation The Period of Social Order in the Era of the Covid-19 Pandemic in Banking In Cliff City - Ari Syahputra; Suwadi Suwadi (Enrichment : Journal of Management, 2021)
The government anticipates the impact of the economic slowdown caused by the pandemic through economic stimulus through the Financial Services Authority (OJK) by issuing Financial Services Authority Regulation (POJK) Number 11/POJK.03/2020 concerning National Economic Stimulus. This regulation relates to policies that support economic growth stimulus that can be carried out by banks. One of them is the policy of restructuring credit or financing. This study aims to analyze the implementation of credit restructuring during the social order era of the covid-19 pandemic at Bank Sumut Tebing Tinggi Branch. This study uses a qualitative approach, where the data used are primary data and secondary data. Primary data were obtained from in-depth interviews with the head of the marketing section and the credit account officer (AO) of Bank Sumut, Tebing Tinggi Branch. Secondary data were obtained from various literatures such as laws, regulations and bank statements. The results of the study indicate that the implementation of credit restructuring at Bank Sumut Tebing Tinggi Branch is carried out in accordance with applicable laws and regulations and is carried out through delays in payment of principal and loan interest installments, extension of credit period, Scheduling of payment of principal and/or loan interest installments and Reduction fine.